Relation of pilot hours of flight to stress, bruxism, attrition and abfraction in vivo research - Puspithasari, Amelia; Suwartini, Tien (Odonto : Dental Journal, 2023)
Background: Pilots are a very stressful job. As a consequence of stress, pilots practice bruxism. Common clinical manifestations due to bruxism are attrition and abfraction. To evaluate whether there is a relationship between pilot flight hours and job stress associated with the occurrence of bruxism, attrition and abfraction among domestic civil aviation pilots throughout Indonesia. Methods: The subjects of the study were 196 pilots who were undergoing routine annual dental examinations at the Aviation Health Center of the Directorate General of Transportation. The pilot's flying hours, pilot job stress, awareness of the occurrence of bruxism was evaluated using the questionnaires. Attrition and abfraction were calculated based on scoring. Results: Most of the research subjects had flight hours of 5,000 to 10,000 hours, namely 44.4% (n = 87). Pilots who experienced stress were represented with at least 56.1% depression (n = 110) and minimal anxiety 49% (n = 96). Bruxism was found in 16.8% (n = 33) of all subjects. The highest attrition measurement was in enamel 47.4% (n = 93) and the most abfraction occurred in posterior teeth 8.2% (n = 16). The results of the Spearman correlation test show that there is no significant relationship between pilot flying hours with stress, bruxism with stress and stress on attrition. Conclusion: The higher the pilot's flight hours, the lower the stress. The higher the pilot's stress, the lower the attrition. There is no relationship between bruxism and pilot stress. The attrition that occurs is not directly related to bruxism activity.